DFIG integration with ReLIFT converter for grid-connected systems: ANFIS MPPT control - Aravindhan Karunanithy; Chidambararaj Natarajan; Sanjay Selvan Arul Manimaran Malathy; Siva Malavan Elantherayan Sharmila (Institute of Advanced Engineering and Science, 2026)
Although dispersed generation and non-linear loads provide difficulties for contemporary power systems that depend on power electronics, renewable energy sources (RES) are essential for meeting the world’s energy demands. This paper provides a unique method for maximum power point tracking (MPPT) in doubly fed induction generators (DFIG) system using an Adaptive network based fuzzy inference system (ANFIS) inference system. The suggested ANFIS MPPT controller adaptively modifies discontinuous control gain to reduce chattering phenomena in the excitation system while preserving the resilience of the closed-loop system. Prior to using a DQ control theory controller for rotor magnitude adjustment to accomplish vector control of active and reactive power, the turbine and DFIG must be modeled. The converter maximizes output current while striving for unity power factor and allowable harmonic content.